Mesenchymal Stem Cells Stabilize Axonal Transports for Autophagic Clearance of α‐Synuclein in Parkinsonian Models. (27th June 2017) - Oh, Se Hee; Lee, Seok Cheol; Kim, Dong Yeol; Kim, Ha Na; Shin, Jin Young; Ye, Byoung Seok; Lee, Phil Hyu
Abstract: Genome‐wide association studies have identified two loci, SNCA and the microtubule (MT)‐associated protein tau, as common risk factors for Parkinson's disease (PD). Specifically, α‐synuclein directly destabilizes MT via tau phosphorylation and induces axonal transport deficits that are the primary events leading to an abnormal accumulation of α‐synuclein that causes nigral dopaminergic cell loss. In this study, we demonstrated that mesenchymal stem cells (MSCs) could modulate cytoskeletal networks and trafficking to exert neuroprotective properties in wild‐type or A53T α‐synuclein overexpressing cells and mice. Moreover, we found that eukaryotic elongation factor 1A‐2, a soluble factor derived from MSCs, stabilized MT assembly by decreasing calcium/calmodulin‐dependent tau phosphorylation and induced autophagolysosome fusion, which was accompanied by an increase in the axonal motor proteins and increased neuronal survival. Our data suggest that MSCs have beneficial effects on axonal transports via MT stability by controlling α‐synuclein‐induced tau phosphorylation, indicating that MSCs may exert a protective role in the early stages of axonal transport defects in α‐synucleinopathies. Stem Cells 2017;35:1934–1947 Abstract : Mesenchymal stem cell (MSC) and its derived soluble factor, eukaryotic Elongation Factor 1A‐2, stabilized microtubule (MT) assembly by decreasing α‐synuclein‐induced tau phosphorylation in parkinsonian models. In addition, MSC enhanced MT‐based axonal transport and led to increased neuronal viability via autophagolysosome‐dependent clearance of α‐synuclein.